The road to Cancun will the Doha round be good for development?. ([Place of publication not identified] Quaker Peace & Social Witness, 2003)
In September the World Trade Organisation (WTO) will hold its fifth Ministerial conference in Cancun, Mexico. The meetings will serve as an opportunity to take stock of progress on the Doha Development Agenda 1 and will likely establish a framework for the completion of the Doha round. They may also see agreement for new issues such as investment and government procurement added to the areas already governed by WTO regulations. This briefing gives an overview of the current state of play in negotiations around some key development related issues that are likely to come under discussion at Cancun.
Includes bibliographical references.
Keywords: Free trade; Doha Round; International trade